Expanding Equitable Access or Exacerbating Existing Barriers? Re-envisioning Online Learning in the COVID-19 Era (Comparative & International Education Series, 2021)
It’s time for a check-up. The COVID-19 pandemic has prompted institutions of higher learning to re-envision the structure and delivery of online learning and its support services. One pressing concern for the foreseeable future is how these changes can potentially exacerbate existing barriers for vulnerable and underrepresented students, such as first-generation, undocumented, indigenous, and international students, as well as those with varying abilities. In this chapter, we draw on a critical review of the international literature on online learning and equity in order to identify the potential pitfalls of overlooking the needs of vulnerable populations in the wholesale transition to online instruction. We then explore how institutions can address these issues of equity and social justice in the wake of COVID-19, as expanding equitable access is paramount to the re-envisioning process the pandemic has finally forced educators to take.